The effect of peer support on HbA1c levels in middle-aged and elderly patients with type 2 diabetes: a systematic review and meta-analysis - Luo, Jiankun; Shu, Jiyuan; Pan, Weiqing; Guan, Duanqin; Liang, Congmin; Zheng, Dongyan; Huang, Kailun; Lai, Yixi; Meng, Bing; Lu, Renjian; Cai, Ziwei; Xing, Lifei; et al. (PeerJ, 2025)
Background Peer support is increasingly recognized as a valuable method for managing blood glucose levels and reducing the risk of chronic complications in patients with diabetes. This systematic review and meta-analysis specifically evaluated the effect of peer support on HbA1c levels in middle-aged and elderly patients with type 2 diabetes and explored the potential benefits of peer interactions on glycemic control. Methodology A comprehensive search was conducted across six databases from January 2018 to July 2023, with a focus on randomized controlled trials (RCTs) that compared peer support interventions to standard diabetic care in adults. Among the 3,395 articles identified, eleven studies involving 2,187 participants were included. The quality of each study was assessed using the Cochrane risk of bias tool. A random-effects model was employed to calculate the mean difference (MD) in HbA1c changes, with additional subgroup analyses for specific contexts. Results The findings revealed a modest but statistically significant improvement in HbA1c levels in groups receiving peer support (MD: −0.20; 95% CI [−0.37 to −0.02]; p = 0.03). More pronounced benefits were observed in interventions conducted within formal medical settings, those involving high-frequency contact, and those in group sessions, particularly among elderly patients. Conclusions The results suggest that while peer support provides a slight improvement in HbA1c levels, other intervention strategies—such as frequent contact, group sessions, and formal medical settings—may offer greater glycemic control benefits in elderly patients with type 2 diabetes. These findings support incorporating peer support into diabetes care and underscore the need for further research with larger samples and standardized protocols.
Keywords: Peer support; Type 2 diabetes; Middle-aged and elderly patients; Systematic review; Meta-analysis